Multi-objective optimisation for response reduction of dynamically similar adjacent buildings with optimal VE dampers. (27th May 2022) - Ramakrishna, Uppari; Mohan, S.C.; Patil, Mahesh B.
Over the past two decades, researchers have shown a considerable interest on the seismic protection of adjacent dissimilar buildings through connected control. Applying connected control to adjacent similar buildings remains a challenging process due to in-phase behaviour. However, connected control with varied damper configurations has a scope in its application to identical buildings. Moreover, the seismic protection for adjacent buildings individually will be uneconomical. Therefore, focus of the present study is on the optimal configuration of visco-elastic dampers for seismic response reduction of similar adjacent buildings. Four sets of buildings with different heights, each set with two RC adjacent similar buildings are considered. To obtain optimum location of dampers, two objective functions, top floor displacements of adjacent buildings, are simultaneously minimised using multi-objective particle swarm optimisation. This technique proved to be more effectual in considerably improving the seismic performance for high raised buildings compared to low raised buildings.